International Capital Markets : Developments, Prospects, and Key Policy Issues (September 2000). (World Economic and Financial Surveys; World Economic and Financial Surveys ;, 2000)
Following a review and assesment of recent developments in capital market and banking systems, this year's International Capital Markets report review and assesses recent developments in mature and emerging financial markets and continues the analysis of key issues affecting global financial markets. It examines the systemic implications of the continued rapid development of the global over-the-counter derivatives markets and the expansion of foreign-owned banks into emerging markets. The report also analyzes market participants assessments of the proposals for private sector involvement in the prevention and resolution of crises.